1957
DOI: 10.1002/ange.19570691103
|View full text |Cite
|
Sign up to set email alerts
|

Die Synthese der Fettsäuren mit gereinigten Enzymen des Fettsäurecyclus

Abstract: Gruppe rnit der Koordinationszahl5 auf. Eine Deutung der Ringabhangigkeit wird vermutlich der Konformationsanalyse vorbehalten sein. Einstweilen kommt dem Alternieren der kinetischen GroBen in Bild 25 noch der Reiz des Ungeklarten zu. Bild 25Chapman-Umlagerung der Cyclanon-oxim-trinitrophenylather in 1.4-Dichlorbutanso). Aktivierungsenergien: 0 -0 ; Fteaktionszeschwindigkeits-Konstanten: ---

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1960
1960
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(22 citation statements)
references
References 8 publications
1
20
0
1
Order By: Relevance
“…The holo-ACP-A or holo-PCP were separated from phosphopantetheinyltransferase by nickel ion affinity chromatography. Confirmation that at least 90% of the apoforms had been converted to the corresponding holoforms was obtained by incubation of a portion of the product with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetyl-CoA and human phosphopantetheinyltransferase and assaying the incorporation of radiolabel into the ACP (only residual apoform is radiolabeled by [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetyl-phosphopantetheine transfer (24)). …”
Section: Subcellular Fractionation Of Sf9 Cells Expressing the Full-lmentioning
confidence: 99%
See 1 more Smart Citation
“…The holo-ACP-A or holo-PCP were separated from phosphopantetheinyltransferase by nickel ion affinity chromatography. Confirmation that at least 90% of the apoforms had been converted to the corresponding holoforms was obtained by incubation of a portion of the product with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetyl-CoA and human phosphopantetheinyltransferase and assaying the incorporation of radiolabel into the ACP (only residual apoform is radiolabeled by [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetyl-phosphopantetheine transfer (24)). …”
Section: Subcellular Fractionation Of Sf9 Cells Expressing the Full-lmentioning
confidence: 99%
“…Indeed one laboratory reported that short and medium chain-length fatty acids could be produced using the partially purified mitochondrial ␤-oxidation enzymes, ␤-ketoacyl thiolase, ␤-hydroxyacyl-CoA dehydrogenase, enoyl-CoA hydratase, and enoyl-CoA reductase (4), and another found that inhibitory antibodies to pig heart 3-ketoacyl-CoA thiolase inhibited, in a parallel fashion, the fatty acid elongation system of pig heart mitochondria (5). The picture was complicated by reports that liver and heart mitochondria have two distinct fatty acid-synthesizing systems, one acetyl-CoA-dependent, possibly involving some of the ␤-oxidation enzymes, the other malonyl-CoA-dependent and apparently resembling the cytosolic FAS 1 system. Most studies were in agreement that the acetyl-CoA-dependent system was an elongation pathway in which one or more C 2 units, derived from acetyl-CoA, were added to preexisting saturated and unsaturated fatty acids of a broad range of chain length (C 6 -C 20 ).…”
mentioning
confidence: 99%
“…But after treatment of the homogenate with deoxycholic acid [23], structural enzymes may be dispersed and assayed by the more convenient and rapid optical assay according to Warburg [24]. This method was also applied to assays of the transport ATPase.…”
Section: Assaymentioning
confidence: 99%
“…Cholesterol (Bucher & McGarrahan, 1956) and fatty acids (Langdon, 1955;Seubert, Greull & Lynen, 1957) have been shown to be synthesized in vitro by homogenates of mammalian liver from which the heavier subcellular particles have been removed. We have therefore studied cholesterol and fatty acid synthesis in such preparations, obtained from the livers of thyroxine-treated and normal rats.…”
mentioning
confidence: 99%